Community-Based Essential Newborn Care Practices and Associated Factors among Women of Enderta, Tigray, Ethiopia, 2018 - Weldeargeawi, Gebrehiwot Gebremariam; Negash, Zenawi; Kahsay, Alemayehu Bayray; Gebremariam, Yemane; Tekola, Kidanemaryam Berhe (International Journal of Reproductive Medicine, 2020)
Introduction. Neonatal mortality contributes a higher percentage of infant mortality, especially in developing countries including Ethiopia where the rate of institutional delivery is low. In Ethiopia, scientific evidences on the level of community-based essential newborn care practice were scanty and inconclusive. Objectives. The aim of the study was to assess community-based essential newborn care practices and associated factors among women who have infant<12 months. Methods. A community-based cross-sectional study was employed among 634 randomly selected women who have infant<12 months from June 23, 2017, to August 29, 2017, at Enderta district. Data was collected by a face-to-face interview through structured questionnaires, and it was coded, entered, and cleaned using EpiData version 3.1. Then, the data was exported to SPSS version 21 for analysis. Odds ratios and p value were computed to know the association between the independent variables with the dependent variable. Finally, a variable at p values of p<0.05 was considered statistically significant with the outcome variable. Result. The overall community-based essential newborn care practice was found 40.7%. Educational status (AOR=6.6, 95% CI, 2.49-11.97), previous ANC follow-up (AOR=1.7, 95% CI, 1.2-3.80), weight of the child during birth (AOR=1.3, 95% CI, 1.12-2.98), and place of delivery (AOR=2.1, 95% CI, 1.50-4.63) were found to be significantly associated with community-based essential newborn care. Even though overall newborn practice was found to be good, the cord care practices were found to be poor that indicated there is a need to rise community awareness.